Synthesis and Characterization of Nickel-Alumina Composites from Recycled Nickel Powder - V. G. Karayannis; A. K. Moutsatsou (Advances in Materials Science and Engineering)
The recycling of metallic waste to create more valuable materials and their valorization into upgraded metal-based composites constitutes an important field of study. The composite industry nowadays considers environmental improvements as important as other properties of the materials. In the present paper, nickel powder was recycled from ferrous scrap, a low-cost and largely available material, by an effective hydrometallurgical recovery process. Then, this recycled powder was successfully used along with particulate α-alumina to prepare oblong nickel-based composite specimens with ceramic reinforcement loadings ranging from 0 to 30 wt.% by applying powder processing manufacturing techniques including cold isostatic pressing (CIP) and sintering. The microstructures obtained were characterized, the specimens were subjected to three-point bend tests, and their fracture behaviour was evaluated. By increasing the % ceramic reinforcement content, density clearly decreases while strengthening is achieved, thus leading to development of lightweight and enhanced oblong nickel-alumina composites. The composite microstructure, and particularly the metal-ceramic interface bonding, has a strong impact on fracture behaviour upon external loading.